Advances in in vivo Non-invasive Delivery of Gentamicin - Bhattacharjee, Arka; Chakraborty, Arpan; Chaulya, Nitai Chand; Mukhopadhyay, Goutam (Indian Journal of Pharmaceutical Education and Research, 2023)
Introduction: Parenteral administration of gentamicin is a globally known therapeutic strategy for severe infections, including severe community acquired pneumonia, complex severe acute malnourishment, neonatal and pediatric sepsis. The drug is also prescribed as an ophthalmologic anti-infective. In most cases, the therapeutic course necessitates frequent bolus medication doses, lengthy hospitalization, and ongoing therapeutic monitoring; hence a qualified healthcare provider is required. Objectives: Gentamicin is a hydrophilic drug and has a short half-life, making it difficult to achieve appropriate systemic concentrations when taken parenterally. The use of innovative oral medication delivery systems is justified in this context. Furthermore, new delivery strategies can increase the membrane permeability of gentamicin. Conclusion: The current analysis provides a detailed summary of gentamicin's research history as well as several developing drug delivery strategies that have been explored. The examples included in the paper give important evidence on innovative delivery systems for gentamicin in the domain of antimicrobial investigations opening a way for upcoming therapeutics that may provide better clinical outcomes.
Keywords: Gentamicin; Non-invasive; Aminoglycoside; Bioavailability; Permeability